E - UMKM Studi Kasus Penjualan Kain Tenun Berbasis Android dengan Metode Waterfall - Godifridus Metboki; Darsono Nababan; Yoseph P.K. Kelen (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2024)
Insana Woven Fabric is a local craft originating from NTT whose manufacturing technique is by embroidering this woven fabric made in a maubesi village located in the TTU district area by the UMKM kube motif group. For the sales method, usually directly, namely from home, some are taken to traditional markets or there are several customers who are outside the NTT area who usually place orders through social media such as Facebook, this causes inefficient sales. The shortcomings of the sales method via social media are information about stock items that still have to be updated manually by the admin so that stock information is not necessarily valid due to human error, for the purchase history must also be recorded manually through the comment column or inbox on social media which results in the craft manager having difficulty in managing financial information.  Based on the existing conditions, it is necessary to engineer an Online Sales Application of Typical Local Crafts of East Nusa Tenggara (NTT) Maubesi Village Case Study. This application is made using android, so that it can be used as an alternative to help the Maubesi village community in selling local handicrafts of the NTT community so that this umkm group is more efficient in the sales process and reaches all buyers inside and outside the NTT area. the method used is waterfall where this implies that the community is more efficient in selling local handicrafts.